Aromatic amino acid metabolites alter interferon signaling and influenza pathogenesis - Anand, Gautam; Clark-Dinovo, Colin; Perry, Alexandra M.; Goodwin, Victoria M.; St. Raymond, Emma; Sakleshpur, Sonia; Steed, Ashley L. (Frontiers in Molecular Biosciences, 2024)
The ability of gut microbial metabolites to influence the host is increasingly recognized. The microbiota extensively metabolizes the three aromatic amino acids, tryptophan, tyrosine, and phenylalanine.Previously we have found that a metabolite of tyrosine, 4-OH-phenylpropionic acid, can enhance type I interferon (IFN) signaling and protect from influenza pathogenesis in a murine model (Steed et al., 2017).Herein we screened 17 related aromatic amino acid metabolites for effects on IFN signaling in human lung epithelial cells and monocytes alone and in the presence of IFN-β, influenza, and LPS. While the tryptophan family metabolites reduced IFN signaling in both cell types, the tyrosine and phenylalanine metabolites had varied effects, which were cell-type dependent. Pooled treatment of all these metabolites reduced IFN signaling in both cell types and suggested a tryptophan metabolite effect dominance. Strikingly, when all the metabolites were pooled together, we found reduced influenza recovery in both cell types. RNA sequencing further validated reduced viral loads and decreased IFN signaling. Single gene silencing of significantly upregulated genes identified by RNA sequencing (EGR2, ATP6V0D2, SPOCK1, and IL31RA) did not completely abrogate the metabolite induced decrease in IFN signaling. However, these upregulated targets suggested a mechanistic link to TGF-beta signaling. Treatment with a TGF-beta inhibitor and combined targeted gene silencing led to a significant reversal of metabolite induced IFN signaling suppression. Finally, we demonstrated that intranasal administration of these metabolites prior to influenza infection led to reduced animal morbidity, viral titers, and inflammation. Our work implies that microbial metabolites can alter IFN signaling mechanistically through TGF-beta and promote beneficial outcomes during influenza infection.